Murder at Honeychurch Hall : a mystery - Dennison, Hannah (Dennison, Hannah. Honeychurch Hall mysteries., 2014)
"Former TV celebrity host Kat Stanford is just days away from starting her dream antique business with her newly widowed mother Iris when she gets a huge shock. Iris has recklessly purchased a dilapidated carriage house, on an isolated country estate, Honeychurch Hall, several hundred miles from London. When Kat arrives at the house, she discovers that Iris has yet another surprise in store. Iris has been writing in secret for years and reluctantly reveals that she's actually Krystalle Storm, the famous bestselling author of steamy bodice-rippers. The gentry upstairs and those below stairs at Honeychurch Hall regard the newcomers with suspicion and distrust. When the nanny goes missing, the loyal housekeeper ends up dead, and Iris is accused of the murder, Kat realizes she hardly knows her mother at all and wonders if she is--indeed--guilty. Although the six hundred year old estate has endured wars, corruption and Royal favors, it's the scandals, secrets and lies of the last few decades that must remain buried at all costs. This is a delightful and traditional cozy mystery that will appeal to fans of Louise Penny and G.M. Malliet"--